2018
DOI: 10.5603/arm.2018.0021
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Veno-Occlusive Disease: Pathogenesis, Risk Factors, Clinical Features and Diagnostic Algorithm—State of the Art

Abstract: Pulmonary veno-occlusive disease (PVOD) and pulmonary capillary haemangiomatosis (PCH) are rare disorders, with the estimated prevalence of less than 1 case per million inhabitants. The vascular pathology in PVOD/PCH involves pre-septal and septal veins, alveolar capillaries and small pulmonary arteries. According to the ERS/ESC classification of pulmonary hypertension (PH) from 2015, PVOD/PCH have been included in the subgroup 1' of pulmonary arterial hypertension (PAH). Recent data indicate, however, the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Unlike IPAH which has a female predominance, PVOD seems to affect men and women equally [27]. Its molecular pathogenesis remains unclear, risk factors such as genetic factors, chemicals and chemotherapies, autoimmunity and inflammation, and cigarette smoking exposure have been reported to be associated with the development of PVOD [1, 5], and three of our patients got tobacco exposure which caused endothelial dysfunction and induced vascular remodeling in animal models of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike IPAH which has a female predominance, PVOD seems to affect men and women equally [27]. Its molecular pathogenesis remains unclear, risk factors such as genetic factors, chemicals and chemotherapies, autoimmunity and inflammation, and cigarette smoking exposure have been reported to be associated with the development of PVOD [1, 5], and three of our patients got tobacco exposure which caused endothelial dysfunction and induced vascular remodeling in animal models of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…We retrospectively reviewed clinical data and outcomes from five PVOD patients hospitalized in the Center for Pulmonary Vascular Diseases (Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing) between May 2009 and March 2018. PVOD was histologically confirmed by extensive involvement of pulmonary veins and venules with fibrous thickening of the intima on lung explants obtained after lung transplantation, or was clinically diagnosed if all following criteria were met: precapillary pulmonary hypertension by right heart catheterization (RHC), presence of two or more radiological characteristics of PVOD on chest high-resolution computed tomography (HRCT) (interlobular septal thickening, centrilobular ground-glass opacities, and mediastinal lymph node enlargement), low diffusing capacity for carbon monoxide, and mutations of the eukaryotic translation initiation factor 2 alpha kinase 4 ( EIF2AK4 ) gene [5]. IPAH was defined by a mean pulmonary arterial pressure (mPAP) ≥25 mmHg at rest with pulmonary capillary wedge pressure ≤ 15 mmHg and pulmonary vascular resistance (PVR) > 3 Wood units, without known causes (connective tissue diseases, HIV infection, portal hypertension, congenital heart diseases and schistosomiasis), as we previously mentioned [68].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in this study, by using samples from both clinical PVOD patients and the MMCinduced PVOD rats, we identified that, a) EndoMT process driven by the activation of TGFβ/Smad3 signalling pathway is likely present in Besides the EndoMT mechanism, non-EndoMT mechanisms have also been extensively studied and proven to participate in and be involved in PVOD disease development, such as the genetic mutation, inflammation and dysregulated immunity, and so forth (Gunther et al, 2019;Montani et al, 2016). The biallelic mutation in EIF2AK4 (encoding general control nonderepressible 2; GCN2) is accomplished with heritable and 10% to 20% cases of the sporadic cases of PVOD (Eyries et al, 2014;Montani et al, 2017;Szturmowicz et al, 2018), which acts more like a cause, but not a consequence of PVOD. However, by using the GCN2 knockout mice, Lu et al showed no significant changes in pulmonary vasculature in comparison to wild-type controls (Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…None of these 6 patients underwent microscopic examination of lung tissues [ 1 ]. In another study, PVOD patients showed no response to PAH target therapy and had the risk of acute pulmonary edema induced by PAH-targeted drugs [ 2 ]. However, the authors showed different results [ 1 ].…”
mentioning
confidence: 99%
“…PVOD is histologically characterized by widespread fibrous intimal proliferation of septal veins and preseptal venules, and is frequently associated with pulmonary capillary dilatation and proliferation [ 4 ]. It shares several clinical and hemodynamic similarities with IPAH, thus often leading to a misdiagnosis as IPAH [ 2 ]. Unlike IPAH, PVOD patients have a dismal prognosis because of the degenerative nature of pulmonary vascular condition and the lack of response to pulmonary vasodilators.…”
mentioning
confidence: 99%